Pengaruh Keterbukaan Ekonomi Dan Ketahanan Eksternal Terhadap Volatilitas Nilai Tukar Rupiah - Dwi Artiaty Nasution; Tri Kunawangsih P (Pusat Riset dan Inovasi Nasional, 2026)
This study aims to examine the effects of economic openness and external resilience on the volatility of the Indonesian Rupiah–US Dollar exchange rate. Economic openness is represented by trade openness and foreign direct investment (FDI), while external resilience is proxied by foreign exchange reserves. In addition, the study investigates the moderating role of foreign exchange reserves in the relationship between economic openness and exchange rate volatility. The research adopts a quantitative descriptive approach using annual time-series data covering the period from 1997 to 2024. The variables analyzed include Rupiah–USD exchange rate volatility, trade openness, foreign direct investment, and foreign exchange reserves. The empirical analysis is conducted using an Ordinary Least Squares (OLS) regression model with an autoregressive AR(1) structure to address the persistence commonly observed in exchange rate volatility. The estimation results indicate that trade openness, foreign direct investment, and foreign exchange reserves individually contribute to reducing exchange rate volatility in Indonesia. These findings suggest that greater economic integration and stronger external buffers play a role in enhancing exchange rate stability. However, the interaction term analysis reveals that foreign exchange reserves do not consistently strengthen the stabilizing effects of economic openness. Under certain external conditions, foreign exchange reserves may instead amplify exchange rate volatility, reflecting the complex dynamics between economic openness and external buffer policies. The results provide important policy implications for managing economic openness and foreign exchange reserves to maintain exchange rate stability in Indonesia.